2017
DOI: 10.1007/s10681-017-1837-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability, heterosis, genetic distance and their intercorrelations for waterlogging tolerance traits in chrysanthemum

Abstract: Waterlogging tolerance (WT) is a major objective in chrysanthemum breeding programs, and although certain genotypes with different tolerance levels have been identified, their value as parents for WT breeding is unknown. Here, twelve F 1 crosses derived from an incomplete diallel mating scheme were conducted to investigate combining ability and heterosis for WT and their relationships with parental genetic distance. The results showed that the membership function value of waterlogging (MFVW) was controlled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
(40 reference statements)
6
31
0
Order By: Relevance
“…Both the distance measures displayed no significant correlation with SCA of all the traits, suggesting genetic distances might not be effective in predicting SCA effects. Our results are in conformity with Su et al [73] who also reported no significant association between genetic distances and SCA in chrysanthemum. However, Tian et al [78], Lariepe et al [44] reported significant correlation between total GD and SCA for length of terminal raceme in rapeseed, for grain yield and plant height in maize, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Both the distance measures displayed no significant correlation with SCA of all the traits, suggesting genetic distances might not be effective in predicting SCA effects. Our results are in conformity with Su et al [73] who also reported no significant association between genetic distances and SCA in chrysanthemum. However, Tian et al [78], Lariepe et al [44] reported significant correlation between total GD and SCA for length of terminal raceme in rapeseed, for grain yield and plant height in maize, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The significantly high SCA effects manifested in desirable direction by low × low testcrosses (poor GCA effects of both male and female parents) for instance Ogu307-33A × DH-18-8-3 for days to 50% CI, Ogu1A × DH-18-8-3 for days to 50% CM, Ogu22-1A × DH-53-6 for GPW and Ogu22-1A × DH-53-6 for NCW may be attributed to dominance × dominance type of interaction having especially complementary epistatic effects [24, 69]. This inconsistent association of GCA and SCA of respective crosses for respective traits is the indication of complex interaction of genes for quantitative traits [73]. Our results are corroborated by the findings of Verma and Kalia [81] for growth and yield traits in cauliflower using SI inbred lines and Singh et al [69] for antioxidant traits using CMS lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations